Adaptive Decision Making and Intellectual Styles - Sofo, Francesco; Colapinto, Cinzia; Sofo, Michelle; Ammirato, Salvatore; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
This exciting publication provides the reader with a theoretical and practical approach to adaptive decision making, based on an appreciation of cognitive styles, in a cross-cultural context. The aim of this Brief is to describe the role of thinking-through different options as part of the decision-making process. Since cognitive style influences decision behavior, the book will first examine thinking styles, which involve both cognitive and emotive elements, as habits or preferences that shape and empower one$1 (Bs cognition and emotion.The information contained in this Brief will be a useful resource to both researchers studying decision making as well as to instructors in the higher education sector and to human resource development practitioners, especially those working in international, multi-cultural companies.s
Keywords: Philosophy (General).; Operations research; Applied psychology; Consciousness; Psychology; Personality and Social Psychology; Industrial, Organisational and Economic Psychology; Operation Research/Decision Theory